Programming Windows NT 4 unleashed - Williams, Mickey (Sams Pub., 1996)
The goal of this book is to bring NT programming topics together under a single title. While Microsoft provides reams of online information regarding NT and NT programming, it is usually at an extra cost to get printed copies of such information. Programming Windows NT 4.0 Unleashed will provide comprehensive, yet succinct, "work around" information unattainable in the online documents.